2005
DOI: 10.1007/s10722-003-6024-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Ratio of Oat (Avena) Protein Fractions of Interest in Coeliac Grain Diets

Abstract: The previously found wide range in the ratios of avenin or methanol-precipitated fractions to residual proteins was revisited by studying 75 oat varieties, mainly representing landraces from Finland, and included old varieties or selections, cv. Kytö, synthetic hexaploid oats and an Avena strigosa line (HA 71-87). The means of the fraction ratios ranged from 4.17 to 6.46 with significant differences. Samples of 10 narrow-ratio and 10 wide-ratio oats were compared more closely. The wide-ratio sample had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…Shan et al (2002) determined that a 33‐amino acid sequence in wheat gluten is responsible for the intestinal damage seen in patients with CD, and work by Arentz‐Hansen et al (2004) showed that a similar 9‐amino acid sequence near the N terminus of avenin proteins can also be toxic to some CD patients. In addition, evidence that some oat varieties are less toxic than others has been presented by Silano et al (2007), Ahokas et al (2006), and Gavriluk et al (2004) Therefore, it was decided to use the 9‐amino acid sequences in primer design to see if the resulting avenin SCARs could also aid breeders in developing oat germplasm more suitable for a gluten‐free diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shan et al (2002) determined that a 33‐amino acid sequence in wheat gluten is responsible for the intestinal damage seen in patients with CD, and work by Arentz‐Hansen et al (2004) showed that a similar 9‐amino acid sequence near the N terminus of avenin proteins can also be toxic to some CD patients. In addition, evidence that some oat varieties are less toxic than others has been presented by Silano et al (2007), Ahokas et al (2006), and Gavriluk et al (2004) Therefore, it was decided to use the 9‐amino acid sequences in primer design to see if the resulting avenin SCARs could also aid breeders in developing oat germplasm more suitable for a gluten‐free diet.…”
Section: Methodsmentioning
confidence: 99%
“…There is also a possibility that functional polymorphisms within avenin loci may directly aff ect phenotypes related to these storage proteins. One such possibility is that variation in avenin proteins among oat cultivars may account for diff erential toxicity in celiac disease (CD; Silano et al, 2007;Ahokas et al, 2006;Gavriluk et al, 2004). Therefore, SCAR markers for avenin proteins might prove useful for fi ngerprinting as well as other applications.…”
mentioning
confidence: 99%
“…До 80% мирового сбора зерна культуры используют на фуражные цели, 20% идет на переработку. Фуражные и пищевые достоинства зерна определяет белок, на 70-80% состоящий из глобулина группы avenalin, и повышенное содержание масла − до 6,2% в пленчатом зерне, до 8% и более в голом [4][5][6]. Масло овса нормализует работу сердца, кровообращение, холестериновый обмен, сдерживает развитие атеросклероза, крахмальные соединения поставляют энергию медленного типа, что позволяет нормализовать уровень сахара в крови диабетиков и не допускать его резких скачков [7].…”
unclassified